Economic empowerment of women in the Islamic world theory and practice - Azid, Toseef; Ward-Batts, Jennifer (Advances in research on Islamic economics and finance, 2020)
"The book, Economic Empowerment of Women in the Islamic World, discusses the economic, social, and political rights and status of women in Islam, which is theoretically given by the Islamic Jurisprudence (Shariah law). The chapters in this volume will address historical practices in comparison to the status of women in the contemporary Muslim world. Men and women in Islam, regardless of their age, social class, and education, are equal as citizens and individuals, but not identical in their rights and responsibilities. It can be observed from Islamic history that in the early age of Islam, women were given full confidence, trust, and high responsibilities in leadership, educational guidance, and decision-making. This volume will try to clarify the confusion in the status of the women in Islam that is presented by the media, as it is assumed that theoretical Islamic empowerment of women bears little relation to the real conditions of women in modern Muslim societies.